Discorsi e pratiche interculturali alla prova del populismo - Colombo, Maddalena; Gilardoni, Guia (SocietàMutamentoPolitica, 2023)
Interculturalism is a way to deal with the cultural difference, which is a growing issue today and often manipulated in politics. In recent years, the populism (along with sovranism, nationalism, and authoritarism) has been the true enemy of the intercultural discourse, widening intolerance and racism in both social interactions, media communication, and urban contexts. The article aims at analyzing the fundamentals of Interculturalism and their apparent discrepancy with populism, providing reflexivity as a remedy to the current loss of sense of the intercultural discourse which sometimes became functional to the institutional racism. Firstly, the article recalls the basic values to understand the different nuances of interculturalism; secondly, it argues that leaving the “passion for interculturalism” up to the practicalities disempowers the intercultural discourse within the ambivalence of the field level. The authors argue about the need to focus also on the intermediate level in which embedding a rigorous discourse, inspired by the “reflexivity” critique. This is applied to the policy making in some crucial social and educational fields. The social planner is meant to use clear “middle ray concepts” and to distinguish the intercultural solutions from the populistic ones, on the basis of 4 antinomies: simplicity vs. complexity; rapidity vs. duration; conflict vs. conciliation; self-centered self vs. decentered self.